Neuregulin-2 Ablation Results in Dopamine Dysregulation and Severe Behavioral Phenotypes Relevant to Psychiatric Disorders - Leiva-Salcedo, D (Nature Publishing Group, 2018)
Numerous genetic and functional studies implicate variants of Neuregulin-1 (NRG1) and its neuronal receptor ErbB4 in schizophrenia and many of its endophenotypes. Although the neurophysiological and behavioral phenotypes of NRG1 mutant mice have been investigated extensively, practically nothing is known about the function of NRG2, the closest NRG1 homolog. We found that NRG2 expression in the adult rodent brain does not overlap with NRG1 and is more extensive than originally reported, including expression in the striatum and medial prefrontal cortex (mPFC), and therefore generated NRG2 knockout mice (KO) to study its function. NRG2 KOs have higher extracellular dopamine levels in the dorsal striatum but lower levels in the mPFC; a pattern with similarities to dopamine dysbalance in schizophrenia. Like ErbB4 KO mice, NRG2 KOs performed abnormally in a battery of behavioral tasks relevant to psychiatric disorders. NRG2 KOs exhibit hyperactivity in a novelty-induced open field, deficits in prepulse inhibition, hypersensitivity to amphetamine, antisocial behaviors, reduced anxiety-like behavior in the elevated plus maze and deficits in the T-maze alteration reward test - a task dependent on hippocampal and mPFC function. Acute administration of clozapine rapidly increased extracellular dopamine levels in the mPFC and improved alternation T-maze performance. Similar to mice treated chronically with N-methyl-d-aspartate receptor (NMDAR) antagonists, we demonstrate that NMDAR synaptic currents in NRG2 KOs are augmented at hippocampal glutamatergic synapses and are more sensitive to ifenprodil, indicating an increased contribution of GluN2B-containing NMDARs. Our findings reveal a novel role for NRG2 in the modulation of behaviors with relevance to psychiatric disorders. © The Author(s) 2018.